Factors Influencing Behavioral Intention to Apply Freemium Services in Islamic Lifestyle Digital Applications Using Unified Theory of Acceptance and Use of Technology (UTAUT) - Timur, Yan Putra; Ratnasari, Ririn Tri; Pitchay, Anwar Allah; Sari, Dyah Permata; Rifqi, Muhammad (Journal of Information Systems Engineering and Business Intelligence, 2024)
Background: Islamic lifestyle digital applications (ILDA) are a sector in the rapidly increasing digital halal media and leisure industry. To ensure sustainable revenue for ILDA developers, freemium strategy needs to be implemented. However, there is a lack of research examining the factors that influence the adoption of freemium strategies in ILDA products. Objective: This research aimed to explore the factors within Unified Theory of Acceptance and Use of Technology (UTAUT) framework that aid ILDA users to use freemium services. Specifically, the research focused on users trust (UT) and users satisfaction (US) as factors influencing the increase in behavioral intention (BI). Methods: Quantitative method was adopted in this context and purposive sampling method was used to obtain 400 data from respondents. The data were then analyzed using Partial Least Square Structural Equation Model (PLS-SEM) method. Results: The results showed that performance expectancy (PE) as well as effort expectancy (EE) positively and significantly influenced US. Similarly, facilitating conditions (FC) and social influence (SI) significantly affected UT. Both UT and US positively influenced users BI toward freemium services. Digital literacy (DL) had a positive moderating effect between PE and business expectations in US, but the effect was not statistically significant. Conclusion: The research described that all UTAUT variables, along with UT and US, influenced the intention to adopt freemium services in ILDA. Moreover, DL did not have any moderating effect on the framework considered in this context. These results signified that users tended to be satisfied and trust the benefits enjoyed, rather than being influenced by DL level.   Keywords: Behavioral Intention, Digital Literacy, Islamic Lifestyle Digital Application, Satisfaction, Trust, UTAUT